Feasibility analysis of household electricity installation in Klambir V village Hamparan Perak district Deli Serdang regency - Adi Sastra Pengalaman Tarigan; M.Rizki syahputra; Muhammad Fahreza (Institute of Computer Science (IOCS), 2023)
Household electrical installations over time experience change both in quality and quantity. The declining quality of electrical installations and changes in the number of load points greatly affect the feasibility of electrical installations and the safety of the users. This research was conducted to know the percentage level of feasibility of household electrical installations and the factors that cause the infeasibility of household electrical installations. This research is a qualitative research study using a descriptive approach which was carried out in Klambir V Village, Hamparan Perak District, Deli Serdang Regency. The objects studied were 20 houses with the sampling technique used in this study used a random sampling technique. The instruments used were observation, interviews, and documentation. The data obtained from this study is the Percentage Level of household electrical installations in Klambir V Village, Hamparan Peraak District, Deli Serdang RegencyGround resistance value is still quite large and categorized as